Educational and Vocational Outcomes of Adults With Childhood‐ and Adult‐Onset Systemic Lupus Erythematosus: Nine Years of Followup. Issue 5 (May 2014) - Lawson, Erica F.; Hersh, Aimee O.; Trupin, Laura; von, Emily; Okumura, Megumi J.; Yazdany, Jinoos; Yelin, Edward H.
<x xml:space="preserve">Abstract</x> Objective To compare educational and vocational outcomes among adults with childhood‐onset systemic lupus erythematosus (SLE) and adult‐onset SLE. Methods We used data derived from the 2002–2010 cycles of the Lupus Outcomes Study, a longitudinal cohort of 1, 204 adult subjects with SLE. Subjects ages 18–60 years living in the US (n = 929) were included in the analysis and were classified as childhood‐onset SLE if age at diagnosis was <18 years (n = 115). Logistic regression was used to assess the unadjusted and adjusted effect of childhood‐onset SLE, sex, race/ethnicity, baseline age, urban or rural location, and US region on the likelihood of completing a bachelor's degree. Generalized estimating equations were used to assess the effect of childhood‐onset SLE, demographics, education, and disease‐related factors on the odds of employment, accounting for multiple observations over the study period. Results Subjects with childhood‐onset SLE were on average younger (mean ± SD 29 ± 10 years versus 44 ± 9 years), with longer disease duration (mean ± SD 15 ± 10 years versus 11 ± 8 years). Subjects with adult‐onset SLE and childhood‐onset SLE subjects were equally likely to complete a bachelor's degree. However, subjects with childhood‐onset SLE were significantly less likely to be employed, independent of demographic and disease characteristics (odds ratio 0.62, 95% confidence interval 0.42–0.91). Conclusion While subjects with SLE are just as likely as those with adult‐onset SLE to complete college education, childhood‐onset SLE significantly increases the risk of not working in adulthood, even when controlling for disease and demographic factors. Exploring reasons for low rates of employment and providing vocational support may be important to maximize long‐term functional outcomes in patients with childhood‐onset SLE.